HEALTH ATTITUDES OF THE FEMALE STUDENTS FROM OLSZTYN, POLAND - THE PHYSICAL ACTIVITY, ADDICTIONS AND THE KNOWLEDGE ABOUT HEALTH BEHAVIORS - Robert Podstawski; Katarzyna Gornik; Ewelina Kolankowska; Michal Boraczynski; Sandra Boraczynska (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
Efforts to improve the health of the population are now focused on promoting healthy lifestyle, improve living conditions and to reduce mortality. Health education activities include regular physical activity, optimal nutrition, reduce addictions and stress. The purpose of the survey conducted among 672 first-year female students at the University of Warmia and Mazury in Olsztyn (Poland) was to determine the attitudes of young women towards a healthy lifestyle. Using anonymous survey questionnaire asked students about the form of physical activity, nutrition, the presence of stressful situations, the use of drugs, such as alcohol and cigarettes, and the interest in deepening knowledge of public health. The majority of students have participated only in obligatory physical education classes in high school and college. They considered that physical activity during the studies should be voluntary. Only 4.24% of students were total abstinence from alcohol, but 79.10% was non-smoking. Many of the women declared the need to change the diet, reducing alcohol intake and give up smoking habit. The students felt that stress connected with attending university is unavoidable, and thus revealed an interest in reducing and limiting mental tension. Despite their young age, students expressed interest in topics such as: first aid course, nutrition, sexuality, and pregnancy problems.